Waconda Springs, Mitchell County - Kelley, Matt (Kansas State University, The Chapman Center for Rural Studies, 2010)
Waconda Springs no longer exists, its memory still lives on. Stories are told by those who remember the sacred site and those who had lived it. Nowadays with all the historical landmark laws, Waconda Springs would have never been bulldozed down. Some say that the legend of the Great Spring just expanded its medicinal powers into Glen Elder Lake, which covers the sacred site today.
Matt Kelley, “Waconda Springs, Mitchell County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/29.
Keywords: Waconda Springs; Mitchell County; Great Spirit Spring; Glen Elder Reservoir; Burnham; Kanza